Doppler estimation and compensation method for underwater target active detection based on communication signal - LU Jun; ZHANG Qunfei; SHI Wentao; ZHANG Lingling (Xibei Gongye Daxue Xuebao, 2021)
The integration of underwater detection and communication uses communication signals to detect a target actively, but the Doppler effect deteriorates the parameter estimation performance of the integrated system. To eliminate the influence of the Doppler effect, a joint Doppler estimation and compensation method based on spectrum zooming and correction is proposed. Firstly, the synchronization signal is used to obtain the signal receiving delay and intercept the single-frequency signal segment in the received signal. Then, the discrete Fourier transform is used to find the frequency that corresponds to the maximum amplitude of the single-frequency signal segment. Finally, the frequency spectrum is refined and corrected within the range near the frequency. The Doppler factor is estimated and the received signal is compensated by the Doppler estimation value. The simulation results show that the proposed method improves Doppler factor estimation accuracy, increases the cross-correlation processing gain and improves DOA (direction of arrival) estimation performance, thus being robust to different Doppler effects.